2010
DOI: 10.1002/cncr.25353
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of multiparameter flow cytometry in the diagnosis of 1013 patients with suspected myelodysplastic syndrome

Abstract: BACKGROUND:The diagnosis and classification of myelodysplastic syndromes (MDS) is based on cytomorphology (CM) and cytogenetics (CG). Multiparameter flow cytometry (MFC) may add important diagnostic information. METHODS: To evaluate the potential role of MFC in the diagnostic setting of MDS, the authors analyzed the results from 1013 patients with suspected MDS by using CM, CG, and MFC in parallel. RESULTS: Concordance between CM and MFC was 82% for diagnostic results in 788 patients who had unequivocal CM res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(55 citation statements)
references
References 38 publications
7
48
0
Order By: Relevance
“…4,5 We incorporated additional antigens, such as CD10, its decrease in granulopoiesis described as loss of synchronicity in relation to other maturation antigens, 7 CD36/CD71 expression on granulopoiesis, reported to correlate with IPSS, 8 and diminished (dim) expression CD71 on nucleated red cells (NRC), known as dyserythropoietic feature. 9,10 For gating strategy and cutoff values see the Online Supplementary Appendix and Online Supplementary Tables S1 and S2.…”
Section: Myelodysplastic Syndromes With a Deletion 5q Display A Charamentioning
confidence: 99%
“…4,5 We incorporated additional antigens, such as CD10, its decrease in granulopoiesis described as loss of synchronicity in relation to other maturation antigens, 7 CD36/CD71 expression on granulopoiesis, reported to correlate with IPSS, 8 and diminished (dim) expression CD71 on nucleated red cells (NRC), known as dyserythropoietic feature. 9,10 For gating strategy and cutoff values see the Online Supplementary Appendix and Online Supplementary Tables S1 and S2.…”
Section: Myelodysplastic Syndromes With a Deletion 5q Display A Charamentioning
confidence: 99%
“…Although a good correlation between the percentage of blasts determined by morphological examination and percentage of CD34 + cells determined by flow cytometry is usually observed, blast enumeration by morphology is the gold-standard method. 4,22 The correct assignment of the percentage of blasts in peripheral blood is also crucial for a correct diagnosis and classification of patients. 23 In our study, we found a fair agreement in peripheral blood blast cell count.…”
Section: Discussionmentioning
confidence: 99%
“…EHEC), malaria or even more pressing cancer [21][22][23]. Along these lines and as flow cytometry is already one of the key diagnostic methods in clinical workflows [24], the use of inherent compound fluorescence could be well extended to antibiotics in general. Many antibiotics are fluorescent [25] and would be fairly easy to screen bacterial, protozal or fungal patient samples for an abnormal reduction of intracellular fluorescence indicating a resistance mechanism aiding the process of precise and functional medication of a patient.…”
Section: Discussion and Further Perspectivesmentioning
confidence: 99%